The littlest pilgrim - Dougherty, Brandi; Richards, Kristen (New York : Scholastic, 2017)
All the other villagers tell Mini that she is too small to help them with their chores, but she is not too small to be kind to another girl she meets.
P-K.
4-5.
Keywords: Size -- Fiction; Pilgrims (New England colonists) -- Fiction; Friendship -- Fiction